The northern Philippine sea a bioregional development communication strategy - Pajaro, Marivic G.; Watts, Paul D.; Ampa, Jaycelle (2013)
The Philippine marine management challenge requires a scaled up ecosystem approach to the biodiversity-based bioregional level used in marine spatial planning. The related communication challenge is being addressed by a currently informal consortium that includes non-government organizations, local government units, as well as state colleges and universities. The evolving communication strategy described here is focused upon considerations that include local government mandates, status of marine development, provinceby- province assessment of coastal economies, cultural relevance, academic programming, and the need for national inputs on counterpart funding. The current work provides a possible model for Philippine application in all marine bioregions. The concept of the bioregional approach was systematically advocated across one bioregion, the Northern Philippine Sea. The Philippine strategy of development communication was used as a template to promote the initiation of a bioregional approach by establishing an initial level of participation involving the provincial governments as well as the state universities and colleges.
Keywords: Territorial waters; Biodiversity conservation; Biogeography